2020
DOI: 10.1093/geronb/gbaa098
|View full text |Cite
|
Sign up to set email alerts
|

A Double Burden of Exclusion? Digital and Social Exclusion of Older Adults in Times of COVID-19

Abstract: The COVID-19 pandemic has excluded older adults from a society based on physical social contact. Vulnerable populations like older adults also tend to be excluded from digital services because they opt not to use the internet, lack necessary devices and network connectivity, or inexperience using the technology. Older adults who are frail and are not online, many of whom are in long-term care facilities, struggle with the double burden of social and digital exclusion. This paper discusses the potential outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
232
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(277 citation statements)
references
References 23 publications
6
232
0
11
Order By: Relevance
“…Given limited digital media literacy (Schreurs, Quan-Haase, & Martin, 2017;Seifert, Cotten, & Xie, 2020), impairments in decision-making processes (Ebner, Pehlivanoglu, Polk, Turner, & Spreng, in press;Spreng, Ebner, Levin, & Turner, 2020), and changes in socioemotional functioning (Ebner & Fischer, 2014;Gutchess & Samanez-Larkin, 2019), older adults may be particularly susceptible to fake news (Brashier & Schacter, 2020;Grinberg, Joseph, Friedland, Swire-Thompson, & Lazer, 2019). In fact, recent statistics showed that older adults were the demographic that shared the most fake news during the 2016 U.S. election on platforms such as Twitter (Grinberg et al, 2019) and Facebook (Guess, Nagler, & Tucker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given limited digital media literacy (Schreurs, Quan-Haase, & Martin, 2017;Seifert, Cotten, & Xie, 2020), impairments in decision-making processes (Ebner, Pehlivanoglu, Polk, Turner, & Spreng, in press;Spreng, Ebner, Levin, & Turner, 2020), and changes in socioemotional functioning (Ebner & Fischer, 2014;Gutchess & Samanez-Larkin, 2019), older adults may be particularly susceptible to fake news (Brashier & Schacter, 2020;Grinberg, Joseph, Friedland, Swire-Thompson, & Lazer, 2019). In fact, recent statistics showed that older adults were the demographic that shared the most fake news during the 2016 U.S. election on platforms such as Twitter (Grinberg et al, 2019) and Facebook (Guess, Nagler, & Tucker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedical solutions are often feasible and acceptable in delivering care to older adults in LTCFs, even in those with sensory impairments such as hearing or visual loss (9). However, older adults are less likely than younger people to be able to take advantage of the opportunities enabled by modern information and communication technology (ICT) or telemedicine (10)(11)(12)(13)(14). Older adults living in LTCFs often (a) opt not to use the internet, (b) cannot afford internet access or ICT devices, (c) lack technical solutions with which to use telemedicine to connect virtually with doctors or other health professionals, (d) have physical or cognitive limitations that may limit possible telemedicine use or prevent them from using telemedicine at all without assistance, and (e) lack the skills to use ICT or telemedicine even if they do have access (9,11,(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…These challenges are associated with the moral imperative to avoid doing harm, respect people's liberty and privacy, (Gostin et al, 2020) and communicators' ethical obligations to sincerity, truthfulness, and comprehensibility (Johannesen et al, 2008). Because inequity concerns are intensified in a pandemic, this calls attention to societies' obligation to consider internet access to use online resources to all as a basic human right, and to provide support systems and skills suited for populations with diverse needs and capacities (Seifert et al, 2020;Watts, 2020). Attending to these ethical concerns has important practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Across and within countries members of certain groups have limited access to digital technologies or limited skills in using them, which are mainly associated with lower income, age, and geographic location (living in rural areas; Watts, 2020). Digital inequality results in unintended consequences, such as when older adults, including those with multiple morbidities and functional impairments, feel more socially excluded than others when required to keep spatial distancing because of their limited participation in the digital world (Seifert et al, 2020). Furthermore, due to the pandemic, people are encouraged to use digital and telehealth services as well as various apps developed to help people cope with mental health issues or promote physical activity.…”
Section: Covid-19 Communication and Inequitymentioning
confidence: 99%